Keanekaragaman Fenotipe Ayam Lokal (Gallus gallus domesticus) di KotaTernate - FATMONA, SARIFFUDIN; Nursjafani, Nursjafani (Cannarium, 2020)
Local chicken is one of the biodiversity that has a significant role in maintaining ecosystem sustainability. Ternate City is one of the regions in Indonesia. Which has a high and typical variety of local chicken. This study aims to determine genetic diversity based on the qualitative traits and morphology of local Kampong Chickens in the city of Ternate, as the basis for efforts to develop local superior livestock. This research was conducted in April to June 2019, the district of Jambula, Kastela, Rua, Taduma, Loto dan Tugafo. The study was conducted using purposive sampling method. The qualitative and morphological characteristics of the 60 samples, namely 30 males and 30 females, had different characters in males and females, but of all the coat colors were more dominant in black coat color, yellowish-white shank color, red comb color, pea comb shape, white ear color and reddish yellow eye color. While the highest body size character of male and female local chicken was found in the femur length of male chicken which was 144,90 %